Matrix Design of Strain Hardening Fibre Reinforced Engineered Geopolymer Composite - Nematollahi, B.; Sanjayan, J.; Shaikh, Faiz (2015)
The feasibility of developing a fiber reinforced engineered geopolymer composite (EGC) exhibiting strain hardening behavior under uni-axial tension has been recently demonstrated. The effect of different alkaline activators on the matrix and composite behavior of such EGC has also been evaluated to enhance its compressive and tensile strengths with relatively low concentration activator combinations. The focus of this study, as a follow up investigation, is to evaluate the quantitative influence of geopolymer matrix properties on the strain hardening behavior of the recently developed fly ash-based EGC with the aim of selecting the appropriate type of geopolymer matrix to manufacture the strain hardening EGC with enhanced elastic modulus while maintaining the tensile ductility behavior of the composite. The effects of water to geopolymer solids ratio, sand size and sand content, as the most significant matrix-related parameters, on the matrix properties including workability, compressive strength, elastic modulus, fracture toughness and crack tip toughness, and the uni-axial tensile performance of the composite were evaluated. Experimental results revealed that lowering the water to geopolymer solids ratio and the addition of sand enhanced the elastic modulus of the geopolymer matrix and composite in all cases. However, the excessive use of fine sand and the use of coarse sand adversely affected the strain hardening behavior of the developed EGC due to the increase of the matrix fracture toughness and the first-crack strength of the composite. Only geopolymer matrices with suitable fracture toughness, as defined by the micromechanics design model, maintained the desirable tensile ductility of the developed fly ash-based EGC.